Florida Consumer Preferences for Indoor Foliage Plant Attributes - Hayk Khachatryan; Alicia Rihn (EDIS)
Consumer demand for indoor foliage plants is decreasing. One strategy to counter decreasing demand is to align products with consumer needs. To explore this strategy, this 4-page fact sheet examines purchasing barriers for indoor foliage plants so that breeders, growers, suppliers, and retailers may develop and promote products to overcome those barriers. This paper also investigates the potential of using novel plant attributes that are not readily apparent in retail outlets to generate consumer interest in indoor foliage plants. Written by Hayk Khachatryan and Alicia Rihn, and published by the Department of Food and Resource Economics, September 2016.